Ethyl 2-(4-bromophenyl)-1-sec-butyl-1H-benzimidazole-5-carboxylate - Arumugam, Natarajan; Ngah, Nurziana; Abd Hamid, Shafida; Abdul Rahim, Aisyah Saad (International Union of Crystallography, 2011)
In the title compound, C20H21BrN2O2, the bromophenyl ring is twisted by 40.13 (8) from the benzimidazole mean plane and the Br atom deviates by 0.753 (1) A ˚ from that plane. The sec-butyl group is disordered over two conformations in a 0.898 (5):0.102 (5) ratio. In the crystal, molecules related by translation along [110] are linked into chains via weak C— H Br hydrogen bonds.